Do Transfer Pricing, Capital Intensity, Institutional Ownership and Managerial Ownership Affect Tax Avoidance: Case Study on the Mining Industry Listed on the Indonesia Stock Exchange (IDX) for 2019-2022 Period - Hafiz, Kamran; Cahyaningtyas, Susi Retna (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to analyze the impact of institutional ownership, managerial ownership, capital intensity, and transfer pricing on tax evasion. This study applies a quantitative method with an associative approach. The data used are secondary data obtained through the analysis of financial statements of mining companies that were active during the period 2019 to 2022 and listed on the Indonesia Stock Exchange (IDX), with data collection techniques through internet searches. Purposive sampling was used to select the sample, and all mining companies listed on the IDX during that time period are included in the study population. Panel data regression of Eviews 10 statistical software was used to analyze the data. The results of the study show that simultaneously, Transfer Pricing, Capital Intensity, Institutional Ownership, and Managerial Ownership have a significant influence on tax avoidance in the mining sector listed on the IDX for the period 2019-2022. Specifically, Transfer Pricing and Institutional Ownership have a negative influence on tax avoidance, while Capital Intensity and Managerial Ownership do not show a significant influence on tax avoidance in the sector.